Unlocking the Potential: immune functions of oligodendrocyte precursor cells - Haroon, Amr; Seerapu, Harsha; Fang, Li-Pao; Weß, Jakob Heinrich; Bai, Xianshu (Frontiers in Immunology, 2024)
Oligodendrocyte precursor cells (OPCs) have long been regarded as progenitors of oligodendrocytes, yet recent advances have illuminated their multifaceted nature including their emerging immune functions. This review seeks to shed light on the immune functions exhibited by OPCs, spanning from phagocytosis to immune modulation and direct engagement with immune cells across various pathological scenarios. Comprehensive understanding of the immune functions of OPCs alongside their other roles will pave the way for targeted therapies in neurological disorders.